Investigating the emerging and future trends of knowledge management in small and medium enterprises: A science mapping approach - Muhammad Ashraf, Fauzi; Zuria Akmal, Saad; Mohd Hanafiah, Ahmad; Muhammad Zorif, Fauzi; Md Faizal, Ahmad (Emerald Publishing, 2024)
Purpose – This study aims to evaluate the knowledge structure of knowledge management (KM) applications within small and medium enterprises (SMEs). In pursuit of excellence, SMEs must adopt KM like large corporations, even with limited resources. Design/methodology/approach – Through a bibliometric approach, this study evaluates current themes based on bibliographic coupling analysis and predicts future trends based on coword analysis. A total of 726 documents and 2,658 keywords were derived from the Web of Science database. Findings – Findings show four clusters in bibliographic coupling and three in coword analysis. A common theme discovered converged on digital technology to ensure SMEs follow current market trends. Research limitations/implications – Advanced application of Industry 4.0 requires digital transformation for SMEs’ pursuit of excellence. Implications include sustaining SMEs through a considerable KM system integrated with digital technology for sustainable business activities. Originality/value – To the best of the authors’ knowledge, this study is among the first to provide a science mapping analysis on KM in SMEs by applying a bibliometric analysis